Synthesis and Antimicrobial Activity of 2-Phenylimino-3-amido-5-aryl/alkylimino-1,3,4-thiadiazolidines - AJMIRE, MANISHA; BERAD, B.N. (Asian Journal of Chemistry, 2010)
Several 2-phenylimino-3-amido-5-aryl/alkylimino-1,3,4-thiadiazolidines (4a-g) have been synthesized by the interaction of 1-aryl-2-thio-bis-urea (2a) and phenylimino cyanodichloride (1) in refluxing chloroform medium followed by basification of resulting compound (3a-g). The compounds (2a-g) have been prepared by the condensation of aryl/alkyl isothiocyanates and semicarbazide. The compounds (4a-g) on acetylation afforded monoacetyl derivatives. The synthesized compounds were assayed for their antimicrobial activity against gram +ve and gram -ve microorganisms.